A Literature Review on the Health and Safety Risks in Small-Scale Renewable Energy Manufacturing: A Public Health Perspective - Suhara, Ade; Wibowo, Cahyo; Dewadi, Fathan (Public Health and Safety International Journal, 2025)
The development of small-scale renewable energy manufacturing in developing countries significantly contributes to sustainable energy access and local economic independence. However, this manufacturing sector poses occupational health and safety (OHS) risks that are often overlooked, particularly regarding chemical exposure, technical dust, and informal working conditions. This article presents a systematic literature review to identify these risks from a public health perspective and assess the social, economic, and regulatory factors influencing working conditions. Findings reveal that OHS aspects are frequently neglected in small-scale renewable energy technology development, potentially leading to long-term health impacts, especially for women and young workers in the informal sector. The article recommends developing contextualized OHS guidelines, safety training programs, and healthy workspace design as mitigation strategies. A cross-sectoral approach involving government, academia, and industry stakeholders is essential to ensure safe and sustainable renewable energy manufacturing.